Handbook of research on integrating digital technology with literacy pedagogies - Lantz, Jessica L. 1985-; Sullivan, Brian A. 1983- (IGI Global, 2020)
"This book examines literacy instruction practices with current digital technologies"--
Description based on title screen (IGI Global, viewed 09/21/2019)
Keywords: Literacy / Study and teaching; Computer-assisted instruction; Critical pedagogy; Computerunterstütztes Verfahren; Pädagogik; Lesekompetenz; Aufsatzsammlung